why does log a + log b = log (ab)

Let log a be some number A and log b be some number B

now the natural log of something is the equivalent of saying a=e^A and b = e^B

So a*b = e^A * e^B which by rules of indices

 = e^(A+B)

Therefore log(ab) = log(e^(A+B))

= A + B = log a + log b 

Answered by Rebecca V. Maths tutor

4080 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Differentiate y=ln(2x^2) with respect to x


Find the derivative of the function y = (2x + 12)/(1-x)


What methods are there for integration?


Find tan(A-B) sec^2(A) - 2tan(A) = 16 && sin(B)sec^2(B) = 64cos(B)cosec^2(B)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences